Money and moralities in contemporary Asia - Hoàng, Lan Anh; Alipio, Cheryll (Transforming Asia., 2020)
This volume provides original, nuanced insights into social meanings of money and wealth in moral economies of Asia. Through case studies from South and Southeast Asia, the collection sheds important light on how the new mobilities and wealth created by neoliberal globalization transform people's ways of life, notions of personhood, and their meaning making of the world. It highlights the moral dilemmas and anxieties emerging from the profound socio-economic transformations that are taking place across the region and deepens our understanding of local cultures as well as the inner contradictions of global capital in Asian contexts. With rich ethnographic insights and a diverse range of empirical contexts, chapters in this volume reveal multifaceted complexities and contradictions in the relationship between money and moralities. Money, they affirm, is not an impersonal, objective economic instrument with homogenizing powers but a culturally constructed and socially mediated currency in which meanings are constantly contested and re-negotiated across time and space.